Resin particle mixture and method for manufacturing the same, as well as method for manufacturing three-dimensional shaped article
Patent Information
- Application Number
- JP2024146517
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-08-28
- Publication Date
- 2025-03-14
AI Technical Summary
【0011】 本発明によれば、炭素繊維を含む樹脂粒子混合物、ならびに樹脂粒子混合物を用いて三次元造形物とした際に、高い機械特性と外観に優れる造形物を得ることができる。
Smart Images

Figure 2025036298000001 
Figure 2025036298000002 
Figure 2025036298000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a three-dimensional object suitable for a wide range of applications, such as automotive, aerospace, industrial, and medical applications, and further to a resin particle mixture that is preferably used as a material for the method, and a method for producing the same. [Background technology]
[0002] Three-dimensional modeling allows for a high degree of freedom in designing shapes, and is therefore widely used in applications such as automobiles, aerospace, industry, and medicine. As such a modeling method, the powder bed fusion method is suitable because it can achieve precision modeling and mechanical strength and does not require support members. The modeling process of the powder bed fusion method is a manufacturing method in which a thin layer formation process in which resin powder is spread into a thin layer and a cross-sectional shape formation process in which a laser beam is irradiated onto the formed thin layer in a shape corresponding to the cross-sectional shape of the object to be modeled, thereby bonding the powder, are sequentially repeated.
[0003] Polyamide 12 resin has been mainly used as the material for the above-mentioned resin powder, however, in recent years, there has been an increasing demand for strength and heat resistance, and there is a demand for the application of highly functional materials such as polyamide resins with high heat resistance and polyarylene sulfide resins, represented by polyphenylene sulfide resins (hereinafter sometimes referred to as PPS resins), which have excellent mechanical properties and heat resistance.
[0004] In powder bed fusion bonding, there is a demand for technology to improve the dimensional accuracy and strength of objects. Specifically, technology has been developed for resin particle mixtures in which resin powder is mixed with fibrous inorganic reinforcing materials such as glass fiber and carbon fiber. In particular, carbon fiber is lightweight yet has high strength and elasticity, and due to its excellent characteristics, it has attracted attention as a resin reinforcing material. When the resin particle mixture containing carbon fiber is fused with the resin particles, the resin impregnates the reinforcing material, providing a reinforcing effect, which is extremely important for its functionality.
[0005] For example, Patent Document 1 discloses a method for producing a molded object having excellent mechanical properties by a powder bed fusion method using particles of polyaryletherketone, polyamide 11, polyamide 12, or the like, and a powder containing carbon fibers or glass fibers having a median length L50 of 20 to 150 μm.
[0006] Patent Document 2 describes that by blending an inorganic reinforcing agent with a maximum dimension of 1 μm to 200 μm with PPS resin particles and using a PPS resin powder mixture as a molding material, a molded product with excellent mechanical strength can be obtained. Here, the maximum dimension in Patent Document 2 refers to the average value of the values measured when any two points on the outer corner contour cleaning are selected so that the distance between them is maximized, and the length is taken as the maximum length. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2007-535585 [Patent Document 2] JP 2017-43654 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, in Patent Document 1, it is believed that milled fibers are used as carbon fibers, but since carbon fibers with a median length L50 of 20 to 150 μm are used without any special treatment, when performing additive manufacturing, the relatively long carbon fibers become entangled and clumps occur, which makes it difficult to laminate the powder surface. In addition, since the maximum dimension in Patent Document 2 is the average value of the values measured when any two points on the contour line of the inorganic reinforcing agent are selected so that the distance between them is the maximum, it is believed that the inorganic reinforcing agent in Patent Document 2 with a maximum dimension of 1 to 200 μm also contains relatively long reinforcing fibers, and as with the invention described in Patent Document 1, there is a problem that clumps are generated by reinforcing fibers with long fiber length, and the appearance is deteriorated by being mixed into the molded object, and further, the mechanical properties are deteriorated due to the clumps.
[0009] In view of the problems associated with the prior art, the present invention aims to provide a method for producing a three-dimensional object that minimizes the occurrence of lumps, has excellent appearance, is lightweight, and exhibits high mechanical properties, as well as a resin particle mixture that is suitably used as a material for the method, and a method for producing the same. [Means for solving the problem]
[0010] As a result of intensive research aimed at solving the above problems, the present invention has been made. (1) A mixture containing thermoplastic resin particles and carbon fibers having an average particle diameter of 1 μm or more and 100 μm or less, wherein the number average fiber length of the carbon fibers is 30 μm or more and 120 μm or less and the number of carbon fibers having a fiber length of 200 μm or more is 5% or less. (2) A resin particle mixture according to (1), which contains 10% by weight or more and 50% by weight or less of carbon fiber, based on 100% by weight of the entire resin particle mixture. (3) The resin particle mixture according to (1) or (2), wherein the average diameter of the carbon fibers is 1 μm or more and 30 μm or less. (4) The resin particle mixture according to any one of (1) to (3), wherein the melting point of the thermoplastic resin particles is 200° C. or higher and 300° C. or lower. (5) A method for producing a resin particle mixture according to any one of (1) to (4), comprising carrying out a step of removing long fibers from carbon fibers to obtain carbon fibers having a number average fiber length of 30 μm or more and 120 μm or less and a number of carbon fibers having a fiber length of 200 μm or more of 5% or less, and then mixing the carbon fibers with thermoplastic resin particles. (6) A method for producing a three-dimensional object by using the resin particle mixture according to any one of (1) to (4). (7) A three-dimensional object obtained by powder bed fusion using the resin particle mixture according to any one of (1) to (4), wherein a test piece having a width of 10 mm, a length of 80 mm, and a thickness of 4 mm is prepared by powder bed fusion so that the 80 mm length direction is parallel to the direction in which a recoater moves (X direction), and the flexural modulus of the test piece in the X direction, as measured in accordance with JIS K7171 (2016), divided by the weight of the test piece is 1100 MPa / g or more. Effect of the Invention
[0011] According to the present invention, a resin particle mixture containing carbon fiber, and when the resin particle mixture is used to form a three-dimensional object, it is possible to obtain a molded object having excellent mechanical properties and appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the present invention will be described in detail with reference to embodiments.
[0013] In the case of the resin particle mixture of the present invention, the lamination thickness is about 0.1 to 0.2 mm when using a typical powder bed fusion bonding method. When the resin particle mixture contains reinforcing materials such as carbon fiber, there is a problem that lumps will form during lamination if the maximum fiber length exceeds the lamination thickness.
[0014] The inventors of the present application therefore discovered that by using a resin particle mixture in which the number of carbon fibers larger than 200 μm is 5% or less, a three-dimensional object with a good appearance can be obtained without lumps, and thus arrived at the present invention.
[0015] The ratio of the number of carbon fibers having a fiber length of 200 μm or more in the resin particle mixture of the present invention is 5% or less. The closer the ratio of the number of carbon fibers having a fiber length of 200 μm or more is to 0%, the more likely it is that lumps will occur. Each component will be described below.
[0016] The resin particles used in the present invention are preferably thermoplastic resins because of their excellent fluidity when melted. Examples of such thermoplastic resins include polyarylene sulfide resins, particularly polyphenylene sulfide resins (PPS), polyamide resins, particularly various nylons, such as nylon 6, nylon 66, nylon 610, nylon 612, nylon 11, nylon 12, and nylon 46, polyesters, such as polybutylene terephthalate resins (PBT), polycarbonate resins (PC), polyimide resins, polyetherimide resins, polymethyl methacrylate, polytetrafluoroethylene resins, polyvinylidene fluoride resins, polyvinyl acetate, polyacetal, polysulfone resins, polystyrene resins, polylactic acid, polycaprolactone, methyl acrylate-methyl methacrylate copolymers, acrylonitrile-styrene copolymers, ethylene-vinyl acetate copolymers (EVA), ethylene resin-acrylic acid copolymers, ethylene-propylene copolymers, and ABS (acrylonitrile-butadiene-styrene copolymers).
[0017] The thermoplastic resin in the present invention may be any of a random copolymer, a block copolymer, and a mixture thereof. Among them, from the viewpoint of mechanical strength, heat resistance, and the like, the melting point is preferably 200°C or higher, more preferably 210°C or higher, even more preferably 220°C, and particularly preferably 230°C. The preferred upper limit of the melting point is preferably 300°C or lower. If the melting point exceeds 300°C, the carbon fibers may easily aggregate due to heat accumulation and become lumps, which may make shaping difficult.
[0018] The melt viscosity of the thermoplastic resin used in the present invention is preferably 150 Pa·s or more and 500 Pa·s or less. If the melt viscosity is less than 150 Pa·s, the strength of the produced three-dimensional object will be low, and if the melt viscosity is more than 500 Pa·s, when the resin powder is melted by irradiating it with laser light, the molten resin will not penetrate into the lower layer, resulting in weak adhesion between the layers and the risk of a significant decrease in the strength of the object in the height direction (hereinafter sometimes referred to as the Z direction).
[0019] Here, the melt viscosity was measured using a Toyo Seiki Capillograph 1C die with a hole length of 10.00 mm and a hole diameter of 0.50 mm. Approximately 20 g of the sample was placed in a cylinder set at a temperature 20°C higher than the melting point of the thermoplastic resin, and the sample was held for 5 minutes, after which the melt viscosity was measured at a shear rate of 1216 sec-1. The preferred lower limit of the melt viscosity is 150 Pa·s, more preferably 160 Pa·s, even more preferably 170 Pa·s, and particularly preferably 180 Pa·s. The preferred upper limit of the melt viscosity is 500 Pa·s, more preferably 450 Pa·s, even more preferably 400 Pa·s, and particularly preferably 350 Pa·s.
[0020] Furthermore, the difference between the melting point and the recrystallization temperature of the thermoplastic resin used in the present invention is preferably 30° C. or more. If the difference between the melting point and the recrystallization temperature of the thermoplastic resin is less than 30° C., the melted resin may shrink or warp due to crystallization caused by laser light irradiation. In powder bed fusion bonding, if the melted resin warps, the warped melted resin may be dragged when a powder layer is laminated on top of the melted resin, making it impossible to obtain a three-dimensional object of the desired shape.
[0021] Here, the recrystallization temperature refers to the apex temperature of the exothermic peak during crystallization when the thermoplastic resin particles are heated in a nitrogen atmosphere using a differential scanning calorimeter from 50° C. to a temperature 40° C. higher than the melting point at a rate of 20° C. / min, held for 5 minutes, and cooled at a rate of 20° C. / min to 50° C. When there are multiple peaks, the apex of the peak on the highest temperature side was taken as the melting point and crystallization temperature.
[0022] The average particle size of the resin particles used in the present invention is more than 1 μm and not more than 100 μm. The preferred lower limit of the average particle size of the resin particles is 3 μm, more preferably 5 μm, even more preferably 8 μm, particularly preferably 10 μm, extremely preferably 13 μm, and most preferably 15 μm. The preferred upper limit of the average particle size is 95 μm, more preferably 90 μm, even more preferably 85 μm, particularly preferably 80 μm, extremely preferably 75 μm, and most preferably 70 μm. If the average particle size of the resin particles exceeds 100 μm, they will not be impregnated well with the carbon fiber, and the uniformity will be lost during powder lamination in a powder bed fusion 3D printer, resulting in a decrease in the strength of the three-dimensional object. On the other hand, if the average particle size of the resin particles is less than 1 μm, the resin particles will aggregate due to static electricity, which will similarly impair the uniformity during powder lamination, resulting in a decrease in the strength of the three-dimensional object.
[0023] The carbon fiber used in the present invention is not particularly limited, and carbon fiber produced by any method can be used, such as PAN-based carbon fiber, pitch-based carbon fiber, etc. The carbon fiber may be in the form of chopped strand or milled fiber, but it is preferable to use milled fiber carbon fiber, since it is preferable that the resin and carbon fiber in the three-dimensional object are uniformly dispersed.
[0024] The carbon fiber of the milled fiber is produced by cutting and pulverizing the carbon fiber chops. A cutting machine or a Tajik rotary cutter is used for cutting, and a pulverizing method of cutting perpendicular to the fiber axis, such as a cutter mill, a jet mill, a turbo mill, or a hammer mill, is used for pulverization. In addition, carbon fiber recovered from used carbon fiber reinforced resin can be used from an environmental perspective. Since commercially available carbon fiber milled fibers usually contain carbon fibers of 200 μm or more, the carbon fiber of the present invention is preferably treated to remove long fibers. In particular, removal of long fibers by a classifier is preferable, and specifically, a dry fine powder classifier such as a sifter, a jet classifier, or a turbo screener is preferable. In order to effectively remove carbon fibers of 200 μm or more using a dry fine powder classifier, it is preferable to use a sieve (screen) with an opening of 45 μm or less, and more preferably an opening of 40 μm or less. If the opening is smaller than 20 μm, the carbon fiber is likely to clog the sieve, making processing difficult.
[0025] The carbon fiber used in the present invention may be subjected to chemical treatment such as coating or etching on the fiber surface in order to enhance adhesion to the resin. The chemical treatment improves adhesion between the resin and the carbon fiber during molding, thereby improving the strength of the three-dimensional object.
[0026] The number average fiber length of the carbon fiber of the present invention is 30 μm or more and 120 μm or less. If it is 30 μm or more, the strength of the molded product can be sufficiently improved, so the lower limit of the number average fiber length of the carbon fiber is preferably 35 μm or less, more preferably 40 μm or less, even more preferably 45 μm or less, and particularly preferably 50 μm or less. If it is 120 μm or less, the carbon fiber can be molded without clumping during powder lamination, so the upper limit is preferably 110 μm or less, more preferably 100 μm, even more preferably 95 μm or less, and particularly preferably 90 μm or less.
[0027] The lower limit of the average diameter of the carbon fiber of the present invention is preferably 1 μm or less, more preferably 22 μm or less, even more preferably 3 μm or less, and particularly preferably 4 μm or less. If it is 1 μm or more, the rigidity of the molded object can be sufficiently improved. The upper limit is preferably 30 μm or less, more preferably 20 μm or less, even more preferably 15 μm or less, and particularly preferably 10 μm or less. If it is 30 μm or less, the fiber length / diameter becomes large, and a sufficient reinforcing effect can be obtained.
[0028] Here, the average fiber length refers to the number-average fiber length, and the average diameter refers to the number-average diameter, and is calculated by measuring the fiber length and diameter of 800 or more carbon fibers randomly selected under a microscope and averaging the values.
[0029] In the present invention, the proportion of carbon fibers having a fiber length of 200 μm or more is 5% or less on a number basis. In the powder bed fusion method, the lamination interval is 100 μm, and fibers having a fiber length of more than 200 μm form fiber clumps during powder lamination, which deteriorates the appearance of the three-dimensional object. Therefore, it is preferable that the proportion of the number of carbon fibers having a fiber length of 200 μm or more is low, and by making it 5% or less, the generation of clumps can be suppressed and a three-dimensional object with a good appearance can be obtained. The proportion of the number of carbon fibers having a fiber length of 200 μm or more is preferably 4% or less, more preferably 3% or less, and particularly preferably 1.5% or less. It is most preferable that no carbon fibers having a fiber length of 200 μm or less are included. Therefore, the lower limit is 0%, which means that no carbon fibers having a fiber length of 200 μm or less are included.
[0030] In addition to carbon fiber, the resin particle mixture of the present invention may contain an inorganic reinforcing material. Examples of the inorganic reinforcing material include talc, silicic acid-containing compounds, minerals, glass fibers, glass beads, glass flakes, expanded glass beads, potassium titanate, carbon nanotubes, carbon black, anthracite powder, titanium oxide, magnesium oxide, potassium titanate, mica, asbestos, calcium sulfite, calcium silicate, molybdenum sulfide, boron fiber, and silicon carbide fiber, and more preferably, glass beads, glass flakes, and glass fibers.
[0031] The mixing ratio of the carbon fiber of the present invention is preferably 1 to 60% by weight, more preferably 10 to 50% by weight, based on 100% by weight of the mixture. If the mixing ratio exceeds 50% by weight, the fluidity of the mixture deteriorates, making it difficult to layer the powder surface in three-dimensional modeling.
[0032] In the present invention, inorganic particles can be added to further improve the fluidity of the resin particle mixture. When the particle size of the resin particles is small, the fluidity of the resin particle mixture deteriorates due to the interaction with neighboring particles, but by adding inorganic particles having a particle size smaller than that of the resin powder, the interparticle distance is increased, and the fluidity of the resin particle mixture tends to be improved.
[0033] The average particle size of the inorganic particles in the present invention is preferably 20 nm or more and 500 nm or less. If the average particle size of the inorganic particles is 500 nm or less, the inorganic particles are easily dispersed uniformly in the resin particle mixture. If the average particle size of the inorganic particles is 20 nm or more, the effect of improving the flowability of the resin particle mixture can be sufficiently obtained.
[0034] The upper limit of the average particle size of the inorganic particles is preferably 400 nm, more preferably 300 nm, particularly preferably 250 nm, and especially preferably 200 nm. The lower limit is preferably 30 nm, more preferably 40 nm, and particularly preferably 50 nm.
[0035] Examples of inorganic particles of the present invention include calcium carbonate particles, silica (silicon dioxide) fine particles, fused silica particles, crystalline silica particles, alumina (aluminum oxide) particles, alumina-containing compound particles, aluminum particles, etc. Silica fine particles are preferred, and among them, amorphous silica particles, which are less harmful to the human body, are extremely preferred from an industrial standpoint.
[0036] The shape of the inorganic particles in the present invention is not particularly limited and may be spherical, porous, hollow, irregular or the like, but among these, spherical is preferred because it exhibits good flowability.
[0037] In this case, the term "spherical" includes not only a perfect sphere but also a distorted sphere. The shape of inorganic particles is evaluated by the circularity when the particles are projected two-dimensionally. Here, the circularity is (the perimeter of a circle equal to the area of the projected particle image) / (the perimeter of the projected particle). The average circularity of inorganic particles is preferably 0.7 to 1.0, more preferably 0.8 to 1.0, and even more preferably 0.9 to 1.0.
[0038] The mixing ratio of the inorganic particles of the present invention is preferably 0.1% by weight or more and 5% by weight or less, more preferably 0.1% by weight or more and 0.3% by weight or less, and even more preferably 0.1% by weight or more and 0.2% by weight or less, based on 100% by weight of the resin particle mixture.
[0039] The method for producing the resin particles of the present invention is not particularly limited, and the resin particles can be particles obtained by polymerization, or particles can be obtained from resin pellets, fibers, or films. In addition, a pulverization treatment described below can be performed depending on the form of the resin particles used. Other examples include a method of dissolving raw materials in a solvent and then spray drying, a poor solvent precipitation method in which an emulsion is formed in a solvent and then contacted with a poor solvent, a submerged drying method in which an emulsion is formed in a solvent and then the organic solvent is dried and removed, and a forced melt kneading method in which a resin component to be granulated and a different resin component are mechanically kneaded to form a sea-island structure, and then the sea component is removed with a solvent. Among these, a pulverization treatment is preferably used from the viewpoint of economy. The pulverization method is not particularly limited, and examples thereof include a disk mill, a jet mill, a bead mill, a hammer mill, a ball mill, a sand mill, a turbo mill, and freeze pulverization. Dry pulverization such as a turbo mill, a jet mill, and freeze pulverization is preferable, and freeze pulverization is more preferable.
[0040] It is important that the mixture of the present invention is uniformly mixed with the resin particles and the carbon fibers. Although the mixing method is not particularly limited, a method of mixing while stirring with a rotating blade or stirring blade is preferable. A mixing method of rotating the container containing the resin particles, carbon fibers, inorganic particles, etc. is preferable in terms of recovery and operation of the mixture. The rotating shaft of the container is not particularly specified, but one having two or more rotating shafts is preferable. The rotation speed of the mixing container is preferably 3.5 rpm or more and 35 rpm or less, more preferably 15 rpm or more and 30 rpm or less, regardless of the rotation direction. The longer the mixing time, the more effective it is for uniform mixing, and 15 minutes or more is preferable, and 20 minutes or more is more preferable.
[0041] In the present invention, it is preferable to use a mixing vessel equipped with a rotating blade or stirring blade inside. By using these, the aggregation of carbon fibers can be eliminated and more uniform mixing is possible. It is preferable that one or more rotating blades or stirring blades are installed per vessel. The rotation speed is preferably 100 rpm or more and 1,000 rpm or less, more preferably 400 rpm or more and 700 rpm or less.
[0042] In the resin particle mixture obtained by mixing resin particles and carbon fibers in the present invention, almost no breakage of carbon fibers occurs when the resin particles and carbon fibers are mixed, so the number average fiber length of the carbon fibers contained in the resin particle mixture is 30 μm or more and 120 μm or less, and the number of carbon fibers with a fiber length of 200 μm or more is 5% or less. The number average fiber length of the carbon fibers in the resin particle mixture and the number of carbon fibers with a fiber length of 200 μm or more are determined by observing the resin particle mixture under a microscope and randomly counting 800 or more carbon fibers, in the same way as when measuring the number average fiber length of the carbon fibers before mixing with the resin particles and the number of carbon fibers with a fiber length of 200 μm or more.
[0043] The method for producing a three-dimensional object of the present invention involves supplying the above-mentioned resin particle mixture to a 3D printer.
[0044] As a method for forming the three-dimensional object of the present invention, powder bed fusion is preferable.
[0045] The powder bed fusion method is a 3D printing technique in which a layer of raw material resin particles is formed, the position corresponding to the cross section of the desired object is melted and welded using a heat source such as a laser, and then a layer of thermoplastic resin particles is formed on top of that, and this process is repeated to obtain a three-dimensional object.
[0046] The method for producing a three-dimensional object of the present invention is a method for producing a three-dimensional object by a powder bed fusion method using the resin particle mixture of the present invention. As a method for producing a three-dimensional object in the powder bed fusion method, a known method can be used, for example, the method described in International Publication No. 2022-250003.
[0047] The resin particles used in the powder bed fusion process can be appropriately recovered and, for example, treated using a sieve with 1 mm mesh to remove molten resin other than the powder, and then reused in the powder bed fusion process, or can be dissolved and precipitated to be powdered and regenerated and reused in the powder bed fusion process, or can be mixed with unused resin particles and reused, or can be recycled as appropriate.
[0048] The carbon fibers contained in the three-dimensional structure obtained by the present invention preferably have a number-average fiber length of 30 μm or more and 120 μm or less, and the number of carbon fibers having a fiber length of 200 μm or more is 5% or less. Since the number-average fiber length of the carbon fibers contained in the structure and the number of carbon fibers having a fiber length of 200 μm or more are 5% or less, the three-dimensional structure of the present invention has excellent mechanical strength and excellent appearance.
[0049] The three-dimensional object of the present invention is a three-dimensional object obtained by powder bed fusion using a resin particle mixture in which a test piece having a width of 10 mm, a length of 80 mm and a thickness of 4 mm is produced by powder bed fusion, with the 80 mm length being parallel to the direction of movement of the recoater (X direction), and the flexural modulus of the test piece in the X direction, measured in accordance with JIS K7171 (2016), divided by the weight of the test piece is 1100 MPa / g or more.
[0050] The value obtained by dividing the flexural modulus in the X direction of the three-dimensional object of the present invention by the weight of the test piece is preferably 1300 MPa / g or more, more preferably 1500 MPa / g or more, even more preferably 1700 MPa / g or more, and particularly preferably 2000 MPa / g or more, in order to provide a three-dimensional object that is lightweight, has high rigidity, and is difficult to deform, so that the three-dimensional object can be used in applications such as automobiles and aerospace. The upper limit is not particularly limited, but since an excessively large elastic modulus generally tends to make the object brittle and reduce its strength, the upper limit is preferably 5000 MPa / g or less, more preferably 4000 MPa / g or less, even more preferably 3500 MPa / g or less, and particularly preferably 3000 MPa / g or less.
[0051] Compared to ordinary melt molding, three-dimensional objects are obtained by crystallization in a process of lowering the temperature at normal pressure at a slow rate, so the state of the crystals is different from that of ordinary melt molding, but it is difficult to express this as a characteristic of the object, so they are limited by the manufacturing method, that is, three-dimensional molding, preferably powder bed fusion bonding. It is well known that ordinary melt molding can obtain molded objects with high mechanical properties and good appearances by diligent study in accordance with the structure of the mold, but in three-dimensional molding that can mold complex shapes, it has not been possible to obtain molded objects with mechanical properties and good appearances using materials containing carbon fibers, and this has only been made possible by the present invention. EXAMPLES
[0052] The method of the present invention will be specifically described below with reference to Examples and Comparative Examples. Various measurement methods and production methods are as follows.
[0053] [Average particle size of resin particles] The average particle size of the resin particles was measured using a laser diffraction / scattering type particle size distribution analyzer (MT3300EXII, manufactured by Nikkiso) and a 0.5 wt% aqueous solution of polyoxyethylene cumyl phenyl ether (product name Nonal 912A, manufactured by Toho Chemical Industry Co., Ltd.) as a dispersion medium. Specifically, a cumulative curve was obtained by analyzing the scattered light of a laser using the Microtrack method, with the total volume of the particles obtained being 100%, and the particle size (median diameter: d50) at the point where the cumulative curve from the small particle size side becomes 50% was taken as the average particle size of the resin particles.
[0054] [Resin melting point] The melting point of the resin particles was measured using about 5 mg of particles under a nitrogen atmosphere using a PerkinElmer DSC7 under the following measurement conditions. -Hold at 50℃ for 1 minute -Heating from 50℃ to 40℃ above the melting point, heating rate 20℃ / min Hold for 5 minutes - From 40℃ higher than the melting point to 50℃, the temperature drop rate is 20℃ / min. The apex of the endothermic peak accompanying melting during heating was taken as the melting point.
[0055] [Measurement of carbon fiber length] The fiber length of the carbon fibers was measured by observation with a microscope (Ni-U manufactured by Nikon Corporation), and the length of more than 800 randomly selected carbon fibers was measured using image analysis software (WinROOF2018 manufactured by Mitani Shoji Co., Ltd.) and the number average fiber length was calculated by calculating the average value. In addition, the ratio of the number of carbon fibers with a fiber length of 200 μm or more was calculated based on the number of fibers with a fiber length of 200 μm or more and the number of fibers measured.
[0056] [Measuring the diameter of carbon fibers] The diameter of the carbon fibers was measured by observation using a microscope (Nikon Ni-U). The short diameter of more than 800 randomly selected carbon fibers was measured using image analysis software (Mitani Shoji WinROOF2018) and the diameter of the carbon fibers was calculated by averaging the values.
[0057] [Removal of long carbon fibers] The carbon fibers in the present invention were subjected to removal of long fibers using a Turbo Screener (Turbo Co., Ltd.) at room temperature and in the atmosphere at a rotation speed of 600 rpm.
[0058] [Mixing method of resin particle mixture] In the present invention, the resin particle mixture was mixed by mixing the resin powder, inorganic particles, and inorganic reinforcing material in a nitrogen atmosphere at room temperature and pressure using a tumbler mixer or cross rotary mixer. The resin particles, inorganic particles, and inorganic reinforcing material were mixed for 20 minutes or more while rotating and revolving under nitrogen atmosphere at room temperature and pressure.
[0059] [Creating 3D objects] Using 10 kg of the resin particle mixture obtained above, a powder bed bonding type 3D printer (Aspect Corporation, Rafael300HT) was used to manufacture a 4mm x 20mm x 155mm three-dimensional model. The setting conditions were as follows: a 60W CO2 laser was used, the stacking height was 0.1mm, the laser scanning interval was 0.1mm, the laser scanning speed was 10m / s, when PPS resin particles were used, the laser output was 35W, and the temperature setting was 260°C, and when polyamide 6 particles were used, the laser output was 16W, and the temperature setting was 205°C. The modeling time was 5 hours. The ISO1A test piece with the long side in the XY plane direction was modeled using a 3D printer, and the obtained test piece was the X-direction test piece. At this time, the formation direction of the powder surface of the device was the X direction, the direction perpendicular to the formation direction was the Y direction, and the stacking height direction was the Z direction.
[0060] [Tensile strength of 3D objects] The tensile strength of the three-dimensional model was measured using a universal testing machine (Tensilon universal testing machine RTG-1250 manufactured by A&D Co., Ltd.) The measurement method was in accordance with ISO-527-1, and the average value of five measurements of the test piece in the X direction was taken as the tensile strength.
[0061] [Flexural modulus per unit weight of 3D model] The flexural modulus of the three-dimensional model was measured using a universal testing machine (Tensilon universal testing machine RTG-1250 manufactured by A&D Co., Ltd.). The measurement method was in accordance with JIS K7171 (2016), and the average value of three measurements of the test piece in the X direction was taken as the flexural modulus. The value obtained by dividing this flexural modulus by the weight of the test piece was taken as the flexural modulus per weight of the three-dimensional model.
[0062] [Example 1] The carbon fiber ("PX35" manufactured by Zoltek Corporation) was sieved with a mesh size of 40 μm to remove long fibers, and carbon fiber with an average fiber length of 55 μm, diameter of 7.2 μm, and a ratio of fibers over 200 μm of 0.24% was obtained. The fiber length distribution of the carbon fiber obtained above is shown in Table 1. This carbon fiber was mixed with PPS resin particles with an average particle size of 52 μm and a melting point of 280°C so that the carbon fiber was 20% by weight per 100% by weight of the mixture. This mixture was used to create a three-dimensional object using a powder bed fusion 3D printer. No lumps were generated when creating the three-dimensional object, and the surface was smooth.
[0063] [Example 2] The long fibers were removed from the carbon fibers using a sieve with 45 μm openings, resulting in carbon fibers with an average fiber length of 110 μm and a ratio of fibers of 200 μm or more of 3.2%. Using this carbon fiber, a three-dimensional object was produced in the same manner as in Example 1, except that the carbon fiber was 30% by weight per 100% by weight of the mixture. No lumps were generated when producing the three-dimensional object, and the surface was smooth.
[0064] [Example 3] The long fibers were removed from the carbon fibers using a sieve with 40μm openings, resulting in carbon fibers with an average fiber length of 55μm and 0.90% fibers over 200μm. This carbon fiber was mixed with polyamide 6 resin powder with an average particle size of 50μm and a melting point of 219℃ so that the carbon fiber was 30% by weight per 100% by weight of the mixture. This mixture was used to create a three-dimensional object using a powder bed fusion 3D printer. No lumps were generated when creating the three-dimensional object, and the surface was smooth.
[0065] [Comparative Example 1] A three-dimensional object was produced in the same manner as in Example 1, except that the long carbon fibers were not removed. The carbon fibers had an average fiber length of 126 μm, and the proportion of fibers longer than 200 μm was 10.3%. When producing the three-dimensional object, lumps were generated, and the surface of the object was roughened by the lumps. The fiber length distribution of the carbon fibers obtained above is shown in Table 1.
[0066] [Comparative Example 2] A three-dimensional object was produced in the same manner as in Example 2, except that the removal of long fibers from the carbon fibers was carried out using a sieve with an opening of 300 μm. The carbon fibers from which the long fibers were removed had an average fiber length of 93 μm, and the proportion of fibers 200 μm or longer was 6.3%. When producing the three-dimensional object, lumps were generated, and the surface of the object was roughened by the lumps.
[0067] [Comparative Example 3] A three-dimensional object was produced in the same manner as in Comparative Example 2, except that polyamide 6 resin powder with an average particle size of 50 μm and a melting point of 219° C. was mixed in. When producing the three-dimensional object, lumps were generated, and the surface of the object became rough due to the lumps.
[0068] [Comparative Example 4] A three-dimensional object was produced in the same manner as in Example 1, except that glass fibers were used instead of carbon fibers.
[0069] <Examples and Comparative Examples> Tables 2 and 3 show the components and their amounts (the numbers for resin particles, carbon fiber, and glass fiber in the tables indicate the content of each component, with the resin particle mixture being 100% by weight). The average fiber length of the carbon fibers and the proportion of fibers 200 μm or longer are the values before mixing with the resin particles.
[0070] Next, a three-dimensional object was produced using the obtained resin particle mixture, and an evaluation was performed. The evaluation results of each of the examples and comparative examples are shown in Tables 2 and 3.
[0071] [Table 1]
[0072] [Table 2]
[0073] [Table 3] [Industrial Applicability]
[0074] The present invention provides a method for producing a three-dimensional object having excellent appearance, as well as a resin particle mixture that is preferably used as a material for the object and a method for producing the same. The present invention can therefore be suitably used in a wide range of applications, such as automotive, aerospace, industrial, and medical applications.
Claims
1. A resin particle mixture containing thermoplastic resin particles having an average particle diameter of 1 μm or more and 100 μm or less and carbon fibers, wherein the number average fiber length of the carbon fibers is 30 μm or more and 120 μm or less and the number of carbon fibers having a fiber length of 200 μm or more is 5% or less.
2. 2. The resin particle mixture according to claim 1, comprising carbon fibers in an amount of 10% by weight or more and 50% by weight or less, based on 100% by weight of the entire resin particle mixture.
3. 2. The resin particle mixture according to claim 1, wherein the carbon fibers have a diameter of 1 μm or more and 30 μm or less.
4. 2. The resin particle mixture according to claim 1, wherein the melting point of the thermoplastic resin particles is 200° C. or higher and 300° C. or lower.
5. The method for producing a resin particle mixture according to any one of claims 1 to 4, comprising carrying out a step of removing long fibers from carbon fibers to obtain carbon fibers having a number average fiber length of 30 μm or more and 120 μm or less and a number of carbon fibers having a fiber length of 200 μm or more of 5% or less, and then mixing the carbon fibers with thermoplastic resin particles.
6. A method for producing a three-dimensional object by using the resin particle mixture according to any one of claims 1 to 4.
7. A three-dimensional object obtained by powder bed fusion using the resin particle mixture according to any one of claims 1 to 4, wherein a test piece having a width of 10 mm, a length of 80 mm and a thickness of 4 mm is produced by powder bed fusion in such a way that the 80 mm length direction is parallel to the direction in which a recoater moves (X direction), and the flexural modulus of the test piece in the X direction, as measured in accordance with JIS K7171 (2016), divided by the weight of the test piece is 1100 MPa / g or more.
Citation Information
Patent Citations
Polyarylene sulfide resin particulate mixture
JP2017043654A
WO2007-535585